2 - Notes sur l’Emigration des Hispano-Mauresques en Afrique du Nord et ses Conséquences dans l’Art industriel Local: by Valérie Gonzalez - Valérie Gonzalez (Africa Development, 1988)
The migration by successive waves of Iberian Moorish peoples from the Iberian Peninsula to North Africa has had economic and social consequences especially on the art Industry, an all time important traditional market of North Africa. As is evident even today, the North African Art Industry was profoundly marked by the contributions of the Arabic Andalusian civilization brought by the migrants. Overall both the urban and rural physionomy of North Africa was modified by this process of migration. The Spanish Moores did not find it difficult to adapt themselves to their new environment since they were all linked by their common muslim background. The impact was more significant on fine jewellery and artistical ly conceived luxurious craftswork which are still to be found in North African ar tisanal production today. Therefore, these productions have nowadays a medieval touch which, even if it seems anachronistic, is nonetheless a precious cultural ad vantage which has to be preserved, a distant souvenir as it is of the prestigious past of western islam with its figurehead, Al-Andalus.